The Role of Holistic Nursing in Enhancing Patient Outcomes - Hend saleh Al-Mutairi; Haya Abdullah Almooh; Amal Abdullah Brahim AlFouzan; Anwar manzil ayed alanizi; Malak Farhan Alenzi; Taghreed hamed Alenizi; Atheer saeed Ali Alshahrani; Radia Ahmad jabir hamdy; Mada Swayed Algezani; Mashael Meshhen Almutiri; Samira Sweileh Al-Mutairi; Sarah Saaed albishi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Holistic nursing, a comprehensive approach to patient care, has emerged as a pivotal strategy for enhancing patient outcomes and promoting overall well-being. By recognizing the interconnectedness of the physical, emotional, social, cultural, and spiritual dimensions, holistic nursing addresses the multifaceted needs of individuals. This paper delves into the role of holistic nursing in enhancing patient outcomes, exploring its principles, practices, benefits, and the factors influencing its adoption within healthcare settings. The principles of holistic nursing include treating the whole person, providing individualized care, emphasizing empowerment and self-care, embracing an integrative approach, and fostering therapeutic relationships. The benefits of this approach encompass improved patient satisfaction, enhanced quality of life, effective symptom management, promotion of self-care and prevention, improved communication and trust, culturally competent care, reduced healthcare costs, and stronger patient-provider relationships. Factors influencing the practice of holistic nursing, such as educational and training opportunities, organizational culture and support, resource availability, nurse-patient relationships, continuous professional development, interdisciplinary collaboration, nurse workload, evidence-based practice, and patient education, are explored in-depth. The paper further outlines strategies for promoting holistic nursing, including curriculum integration, continuing education, organizational policies, interdisciplinary collaboration, patient engagement, evaluation and quality improvement, advocacy and leadership, community partnerships, research, and interprofessional education. By embracing holistic nursing and integrating its principles into clinical practice, healthcare organizations can contribute to improved patient outcomes, enhanced quality of care, and a more positive healthcare experience. Ultimately, holistic nursing represents a comprehensive approach that fosters compassionate, comprehensive, and effective care delivery, acknowledging the complexity and interconnectedness of human beings.